Peningkatan Ekonomi Masyarakat Desa Berbasis Industri Rumah Tangga di Desa Sukasari Kecamatan Cidolog Kabupaten Ciamis - Lala Amelia; Aan Anwar Sihabudin; Irfan Nursetiawan (PT. PENERBIT TIGA MUTIARA, 2024)
The aim of the research is to determine the economic improvement of village communities based on household industries in Sukasari Village, Cidolog District, Ciamis Regency. This research uses a descriptive qualitative research design. Techniques for collecting data were obtained through literature study, conducting interviews with 7 sources, and carrying out participant observation. In carrying out analysis, namely by collecting data, reducing data, presenting data and drawing conclusions. The results of this research are: 1) Improving the Village Community Economy Based on Home Industries in Sukasari Village, Cidolog District, Ciamis Regency is not yet optimal, 2) Obstacles that occur are inequality in internet access, lack of business partners who are able to finance capital, unpreparedness for product digitalization business and the lack of literacy in using online media as promotional and sales literacy. 3) The efforts made are that the Village Government has attempted to facilitate training for home industry business actors in Sukasari Village so that they are able to digitize business products such as using online promotional media, improving packaging design, and marketing online via digital platforms for free.